2018
DOI: 10.3390/s18113808
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Monitoring Cell for Constrained Battery Electrodes

Abstract: Testing of improved battery components and new electrochemical energy storage materials in a coin cell format as a test cell is becoming the state of the art. The pressure on the electrode surfaces inside an electrochemical cell is one of the important parameters for high ionic/electronic conductivity and the cyclic lifetime. A self-designed pressure monitoring cell allows both applying an adjustable pressure and monitoring the state of charge-dependent cell pressure during cycling. The load cell shows a recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In conventional LIBs, the liquid electrolyte can accommodate for volume/morphological changes of the electrode materials. [ 47–50 ] However, in SSBs, where the inorganic SE materials present high mechanical rigidity, severe changes in volume can cause contact loss and particle fracture, thus contributing to capacity fading. [ 51–57 ] These issues can be more strongly pronounced if Ni‐rich layered lithium metal oxide CAMs are used, as they undergo large relative volume changes (Δ V / V > 5%).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…In conventional LIBs, the liquid electrolyte can accommodate for volume/morphological changes of the electrode materials. [ 47–50 ] However, in SSBs, where the inorganic SE materials present high mechanical rigidity, severe changes in volume can cause contact loss and particle fracture, thus contributing to capacity fading. [ 51–57 ] These issues can be more strongly pronounced if Ni‐rich layered lithium metal oxide CAMs are used, as they undergo large relative volume changes (Δ V / V > 5%).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Among the most significant advances so far achieved in monitoring battery cells is the determination of the temperature at the surface and within the cell [3,[10][11][12][13][14][15][16][17]. Another type of battery diagnostic involves the determination of strain and pressure changes by gauge sensors [18][19][20]. Other possible solutions are represented by families of nano-plasmonic sensors [21], acoustic sensors [22], and electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…While this has not been interrogated specifically for Li 2 C 6 O 6 , recent experimental work on the high-pressure behavior of Na 2 C 6 O 6 demonstrated changes in both the crystal structure and electrical conductivity as a function of applied pressure in a diamond anvil cell . Additionally, computational investigations of other cyclic oxocarbons (including deltic, squaric, and croconic acids) have suggested that these materials display interesting mechanical properties at elevated pressures including pressure-dependent phase transitions and negative Poisson’s ratios. Likewise, numerous other works have demonstrated the beneficial impact of high pressures on the electrochemical reversibility and long-term stability of electrode stacks during battery cycling. Thus, the pressure-dependent electrochemical characteristics of oxocarbon materials may be very important in developing strategies to improve their stability and longevity.…”
Section: Introductionmentioning
confidence: 99%